Cognitive ergonomics approach in food packaging design influence on purchase decisions among Klang Valley consumers, Malaysia - Md Yusoff, Irwan Syah; Md Hashim, Azhari; Tai, Jia Yi (Persatuan Ekonomi Pengguna Dan Keluarga Malaysia, 2024)
Food packaging plays a multifaceted role in ensuring food safety, convenience, and marketability, and it acts as a silent salesperson, influencing consumer purchasing decisions in a multitude of ways. Nowadays, consumer practices raise significant public health concerns associated with food packaging. Besides, the main objective was to identify the profile of food packaging design on purchase decisions among consumers in Klang Valley at shopping malls by cognitive ergonomic approach. In this research, the variable studied is to identify packaging graphics, color, font style, materials, and information on consumer purchase decisions in Klang Valley at shopping malls. Data was gathered through questionnaires from 270 respondents drawn from five different shopping mall locations in the Klang Valley and chosen through a multistage cluster sampling method. Furthermore, the data was analyzed using descriptive statistics in the form of mean, percentages, standard deviations, and Pearson correlation analysis. The research found a significant positive relationship between packaging graphics, color, font style, materials, and information and consumer purchase decisions. The research concluded that the packaging graphic design is the most significant factor influencing consumer purchase decisions in Klang Valley shopping malls. This research recommends manufacturers implement cognitive ergonomics in food packaging to optimize usability and minimize cognitive workload.